2014
DOI: 10.1007/s10964-014-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of After-School Programs with At-Risk Youth on Attendance and Externalizing Behaviors: A Systematic Review and Meta-Analysis

Abstract: The popularity, demand, and increased federal and private funding for after-school programs have resulted in a marked increase in after-school programs over the past two decades. After-school programs are used to prevent adverse outcomes, decrease risks, or improve functioning with at-risk youth in several areas, including academic achievement, crime and behavioral problems, socio-emotional functioning, and school engagement and attendance; however, the evidence of effects of after-school programs remains equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 61 publications
(107 reference statements)
0
62
0
6
Order By: Relevance
“…Coaching, mentoring, and role modeling Mino Bimaadiziwin, or a good life-which involves sports, team building, and keeping busy with learning activities-is one method of building belonging and offsetting some of the boredom and potential for youth to engage in high risk activities. These ideas are supported in meta-analyses of afterschool programs for vulnerable youth in the U.S., which suggests that non-academic activities may also have a positive impact on the developmental outcomes of young people (Durlak, Weissberg, & Pachan, 2010;Kremer, Maynard, Polanin, Vaughn, & Sarteschi, 2015). Likewise, in their case studies of Indigenous high school students, Preston and Claypool (2013) posed the question, "What motivates students to learn" (p.259)?…”
Section: Discussion and Policy Lessonsmentioning
confidence: 97%
“…Coaching, mentoring, and role modeling Mino Bimaadiziwin, or a good life-which involves sports, team building, and keeping busy with learning activities-is one method of building belonging and offsetting some of the boredom and potential for youth to engage in high risk activities. These ideas are supported in meta-analyses of afterschool programs for vulnerable youth in the U.S., which suggests that non-academic activities may also have a positive impact on the developmental outcomes of young people (Durlak, Weissberg, & Pachan, 2010;Kremer, Maynard, Polanin, Vaughn, & Sarteschi, 2015). Likewise, in their case studies of Indigenous high school students, Preston and Claypool (2013) posed the question, "What motivates students to learn" (p.259)?…”
Section: Discussion and Policy Lessonsmentioning
confidence: 97%
“…Various definitions of communitybased youth programs are used, however, for the purposes of this study, we define them as organized programs supervised by adults that usually occur outside of regular school classes and involve more than one activity (adapted from Kremer et al 2015). Programs that were delivered primarily by teachers during school hours were not included, nor were community-based parenting programs involving young people and their families.…”
Section: Current Studymentioning
confidence: 99%
“…However, not all evaluation studies have shown benefits. A meta-analysis of 24 after-school programs (including both academic and non-academic programs) with at-risk youth was conducted by Kremer et al (2015). Nearly all of the included studies, apart from one, originated in the US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After-school programs are diverse with only some programs including physical activity and few having adequately trained teachers [15,16]. For those afterschool programs that do include physical activity, increasing children's levels of moderate-to-vigorous physical activity to recommended levels has been difficult [16,17].…”
mentioning
confidence: 99%